Performance in written language and arithmetic: relationship between screening (subitems of the Neupsilin-Inf test) and assessment (Research, Society and Development, 2022)
Introduction: mastering writing and performing well in arithmetic are highly valued in our culture and a factor that interferes in people's financial capacity and, therefore, in their quality of life. Early detection of children at risk for writing/arithmetic language disorders is therefore necessary. Objective: relating performance on a written language/arithmetic screening test and the result of the detailed assessment of these skills. Method: twenty-five children (10 females; mean age of 8.7 years and standard deviation of 1.1) from a public school participated in the study. These were submitted to two stages of evaluation, the first being a screening of oral/written language and arithmetic skills (dimensions of the Neupsilin Child, ou  ou Neupsilin-Inf test, test) and, in the second stage, a detailed assessment of reading, writing and arithmetic (use of standardized tests ). For statistical inference, Fisher's exact test was used (α = 0.05). Results: the association was significant between the oral/written language screening and the results in the reading and writing tests, that is, the children who failed in these dimensions of the screening were the children with alterations in reading and writing tasks, however, between the result of the arithmetic skills screening test and the performance on the arithmetic test, the association was not significant. Conclusion: the screening test used in this study was effective in selecting children with reading or writing problems, but it was not the best way to assess the arithmetic skill.